Effect of HLA-G5 Immune Checkpoint Molecule on the Expression of ILT-2, CD27, and CD38 in Splenic B cells - Hana Rohn; Cordula Lang; Sabine Schramm; Falko M. Heinemann; Mirko Trilling; Anja Gäckler; Oliver Witzke; Peter A. Horn; Vera Rebmann (Journal of Immunology Research)
The human leukocyte antigen G (HLA-G) is an immune checkpoint molecule with a complex network of interactions with several inhibitory receptors. Although the effect of HLA-G on T cells and NK cells is well studied, the effect of HLA-G on B cells is still largely elusive. B cells are of particular interest in the context of the HLA-G-ILT-2 interaction because the ILT-2 receptor is constitutively expressed on most B cells, whereas it is only present on some subsets of T and NK cells. To characterize the effect of HLA-G5 molecules on B cells, we studied splenic B cells derived from cytomegalovirus (CMV) sero-positive donors after CMV stimulation with antigens in the presence and absence of soluble HLA-G5. In the presence of HLA-G5, increased expression of the ITIM-bearing Ig-like transcript (ILT-2) was observed on B cells, but its expression was not affected by stimulation with CMV antigens. Moreover, it became evident that HLA-G5 exposure resulted in a decreased expression of CD27 and CD38 and, accordingly, in lower proportions of CD19+CD27+CD38+ and higher proportions of CD19+CD27-CD38- B cells. Taken together, our in vitro findings demonstrate that soluble HLA-G5 suppresses markers of B cell activation, suggesting that HLA-G5 has an impact on splenic B cell differentiation and activation. Based on these results, further investigation regarding the role of HLA-G as a prognostic factor and a potential therapeutic agent with respect to B cell function appears reasonable.